Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
3. Find the center and the radius of a circle that has the equation [tex]\( x^2 + y^2 = 9 \)[/tex]
To determine the center and radius of the circle from the given equation [tex]\( x^2 + y^2 = 9 \)[/tex]:
- The equation is already in the standard form of a circle equation [tex]\( x^2 + y^2 = r^2 \)[/tex].
Here, [tex]\( r^2 = 9 \)[/tex], so the radius [tex]\( r = \sqrt{9} = 3 \)[/tex].
Since there are no terms with [tex]\( x \)[/tex] or [tex]\( y \)[/tex] shifted by any constants, the center is at the origin.
Center: [tex]\((0, 0)\)[/tex]
Radius: [tex]\(3\)[/tex]
4. Find the center and the radius of a circle that has the equation [tex]\( (x-2)^2 + (y+3)^2 = 144 \)[/tex]
To determine the center and radius of the circle from the given equation [tex]\( (x-2)^2 + (y+3)^2 = 144 \)[/tex]:
- The equation is in the form [tex]\( (x-h)^2 + (y-k)^2 = r^2 \)[/tex] where [tex]\((h, k)\)[/tex] is the center and [tex]\( r \)[/tex] is the radius.
The center [tex]\((h, k)\)[/tex] is at [tex]\( (2, -3) \)[/tex] and the radius is [tex]\( r = \sqrt{144} = 12 \)[/tex].
Center: [tex]\((2, -3)\)[/tex]
Radius: [tex]\(12\)[/tex]
5. Find the center and the radius of a circle that has the equation [tex]\( x^2 + y^2 - 6x - 12y - 55 = 0 \)[/tex]
To determine the center and radius of the circle from the given equation [tex]\( x^2 + y^2 - 6x - 12y - 55 = 0 \)[/tex]:
First, we need to complete the square to rewrite the equation in the standard form of a circle equation [tex]\( (x-h)^2 + (y-k)^2 = r^2 \)[/tex].
1. Rewrite the equation grouping [tex]\( x \)[/tex] and [tex]\( y \)[/tex] terms:
[tex]\[ x^2 - 6x + y^2 - 12y = 55 \][/tex]
2. Complete the square for the [tex]\( x \)[/tex]-terms:
[tex]\[ x^2 - 6x \quad \text{add and subtract} \left( \frac{-6}{2} \right)^2 = 9 \quad \Rightarrow \quad (x - 3)^2 - 9 \][/tex]
3. Complete the square for the [tex]\( y \)[/tex]-terms:
[tex]\[ y^2 - 12y \quad \text{add and subtract} \left( \frac{-12}{2} \right)^2 = 36 \quad \Rightarrow \quad (y - 6)^2 - 36 \][/tex]
Thus, the equation becomes:
[tex]\[ (x - 3)^2 - 9 + (y - 6)^2 - 36 = 55 \][/tex]
Simplify:
[tex]\[ (x - 3)^2 + (y - 6)^2 - 45 = 55 \quad \Rightarrow \quad (x - 3)^2 + (y - 6)^2 = 100 \][/tex]
So, the center of the circle [tex]\((h, k)\)[/tex] is at [tex]\((3, 6)\)[/tex] and the radius is [tex]\( r = \sqrt{100} = 10 \)[/tex].
Center: [tex]\((3, 6)\)[/tex]
Radius: [tex]\(10\)[/tex]
To determine the center and radius of the circle from the given equation [tex]\( x^2 + y^2 = 9 \)[/tex]:
- The equation is already in the standard form of a circle equation [tex]\( x^2 + y^2 = r^2 \)[/tex].
Here, [tex]\( r^2 = 9 \)[/tex], so the radius [tex]\( r = \sqrt{9} = 3 \)[/tex].
Since there are no terms with [tex]\( x \)[/tex] or [tex]\( y \)[/tex] shifted by any constants, the center is at the origin.
Center: [tex]\((0, 0)\)[/tex]
Radius: [tex]\(3\)[/tex]
4. Find the center and the radius of a circle that has the equation [tex]\( (x-2)^2 + (y+3)^2 = 144 \)[/tex]
To determine the center and radius of the circle from the given equation [tex]\( (x-2)^2 + (y+3)^2 = 144 \)[/tex]:
- The equation is in the form [tex]\( (x-h)^2 + (y-k)^2 = r^2 \)[/tex] where [tex]\((h, k)\)[/tex] is the center and [tex]\( r \)[/tex] is the radius.
The center [tex]\((h, k)\)[/tex] is at [tex]\( (2, -3) \)[/tex] and the radius is [tex]\( r = \sqrt{144} = 12 \)[/tex].
Center: [tex]\((2, -3)\)[/tex]
Radius: [tex]\(12\)[/tex]
5. Find the center and the radius of a circle that has the equation [tex]\( x^2 + y^2 - 6x - 12y - 55 = 0 \)[/tex]
To determine the center and radius of the circle from the given equation [tex]\( x^2 + y^2 - 6x - 12y - 55 = 0 \)[/tex]:
First, we need to complete the square to rewrite the equation in the standard form of a circle equation [tex]\( (x-h)^2 + (y-k)^2 = r^2 \)[/tex].
1. Rewrite the equation grouping [tex]\( x \)[/tex] and [tex]\( y \)[/tex] terms:
[tex]\[ x^2 - 6x + y^2 - 12y = 55 \][/tex]
2. Complete the square for the [tex]\( x \)[/tex]-terms:
[tex]\[ x^2 - 6x \quad \text{add and subtract} \left( \frac{-6}{2} \right)^2 = 9 \quad \Rightarrow \quad (x - 3)^2 - 9 \][/tex]
3. Complete the square for the [tex]\( y \)[/tex]-terms:
[tex]\[ y^2 - 12y \quad \text{add and subtract} \left( \frac{-12}{2} \right)^2 = 36 \quad \Rightarrow \quad (y - 6)^2 - 36 \][/tex]
Thus, the equation becomes:
[tex]\[ (x - 3)^2 - 9 + (y - 6)^2 - 36 = 55 \][/tex]
Simplify:
[tex]\[ (x - 3)^2 + (y - 6)^2 - 45 = 55 \quad \Rightarrow \quad (x - 3)^2 + (y - 6)^2 = 100 \][/tex]
So, the center of the circle [tex]\((h, k)\)[/tex] is at [tex]\((3, 6)\)[/tex] and the radius is [tex]\( r = \sqrt{100} = 10 \)[/tex].
Center: [tex]\((3, 6)\)[/tex]
Radius: [tex]\(10\)[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.